2015
DOI: 10.3389/fncel.2015.00110
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the regulation of the Notch signaling pathway are temporally correlated with regenerative failure in the mouse cochlea

Abstract: Sensorineural hearing loss is most commonly caused by the death of hair cells in the organ of Corti, and once lost, mammalian hair cells do not regenerate. In contrast, other vertebrates such as birds can regenerate hair cells by stimulating division and differentiation of neighboring supporting cells. We currently know little of the genetic networks which become active in supporting cells when hair cells die and that are activated in experimental models of hair cell regeneration. Several studies have shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 85 publications
12
118
1
1
Order By: Relevance
“…Studies have shown that upon Wnt stimulation, regeneration is possible in the neonatal cochlea, but this potential is lost after postnatal day 3 (Chai et al, 2012;Cox et al, 2014). Such regenerative failure is linked to changes in the Notch pathway (Maass et al, 2015). Therefore, understanding the gene networks operating from early to late ages might prove informative in assessing feasible approaches to regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that upon Wnt stimulation, regeneration is possible in the neonatal cochlea, but this potential is lost after postnatal day 3 (Chai et al, 2012;Cox et al, 2014). Such regenerative failure is linked to changes in the Notch pathway (Maass et al, 2015). Therefore, understanding the gene networks operating from early to late ages might prove informative in assessing feasible approaches to regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to transdifferentiate in response to Notch inhibition rapidly diminishes following P1 (Maass et al, 2015). In spite of this, we show that bivalency is maintained through P6, consistent with the maintenance of limited transdifferentiation potential in response to Atoh1 ectopic expression (Kelly et al, 2012;Liu et al, 2012a).…”
Section: (N=3) (F)mentioning
confidence: 68%
“…Over the next several days, Atoh1 mRNA levels rise to peak expression around E17.5, before again falling to low levels by P6 (Fig. 1A) (Driver et al, 2013;Maass et al, 2015). To correlate changes in epigenetic status with changes in Atoh1 expression in specific cell types and at different ages, we used fluorescence-activated cell sorting (FACS) to separate prosensory cells prior to the onset of hair cell differentiation, from nascent hair cells that have begun to upregulate Atoh1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations